Manajemen Pelayanan Publik Pada Masa Pandemi Covid-19 di Kelurahan Kaliabang Tengah Bekasi Utara - Albert Panondang Hernando Sihotang; Gili Argentie; Sopyan Resmana Adiarsa (Peneliti.net, 2022)
The problem in the Kaliabang Tengah Village, North Bekasi is the problem of administrative service management during the Covid-19 pandemic when many customers request service. This study aims to analyze the management of public services during the Covid-19 pandemic. The method used for this research is descriptive with a qualitative approach. The findings indicate that the Kelurahan Kaliabang Tengah, Bekasi Utara has made an application to reduce congestion in the implementation of public administration, but the problems that still occur are the lack of public awareness in implementing health protocols and people's disorder when queuing their turn. This is a challenge for the government of Kaliabang Tengah, North Bekasi in solving these problems.